Effect of Family, School, Environment and Personality Factors on Career Awareness and Preference of Secondary School Students in Niger State - Mohammed Mohammed Ndagi; Ibrahim Abdulrahman; Habiba Muhammad Enagi; Dauda Adamu Abubakar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
One of the most challenging issues faced by school leavers is their frequent disappointment with the available job opportunities in the labor market. This often results from not meeting the minimum academic requirements for jobs or realizing too late that they have made poor career choices due to a lack of career awareness. This research aims to investigate the effects of family, school, environment, and personality factors on the career awareness of secondary school students. Primary data were collected by the researcher from seven secondary schools across four educational zones in Niger State, Nigeria, including Minna, Kontagora, Bida, and Suleja. The study employed two research instruments, the Career Awareness Rating Scale and the Career Preference Factor Rating Scale, administered to 382 students, consisting of 212 males and 117 females. Pearson Product-Moment Correlation, mean, and standard deviation were used to analyze the research questions. The findings reveal a significant impact of family, school, environment, and personality on career preference and career awareness among secondary school students. It is recommended, among other things, that counselors should actively engage in providing guidance to parents about the factors influencing their children's career preferences.